Education and Trade Attitudes: Revisiting the Role of Economic Interest. Issue 4 (8th October 2022) - Stiller, Yannick; Dür, Andreas; Huber, Robert A.
Abstract: Why are highly educated people more supportive of international trade? Two competing explanations exist for this empirical finding. On the one hand, the economic interest approach suggests that the highly educated realize that trade can benefit them economically. On the other hand, the ideational perspective argues that this relationship arises because highly educated people are more cosmopolitan, and cosmopolitanism is positively related to support for trade. To contribute to this debate on the education–trade attitude nexus, we present and empirically test four hypotheses. Using data from the PEW Global Attitudes survey (2014) for 36 countries at various levels of development, we find that as expected by the economic interest approach, the effect of education on people's perceptions of the consequences of trade is conditional on respondents' individual and subnational economic context. The results thus show that economic interest at least partly explains education's effects on public opinion towards trade. Beyond adding to this specific debate, the research note makes several broader contributions to research on trade and public opinion.